A novel high-strength polymer hydrogel with identifiability prepared via a one-pot method. Issue 23 (4th May 2017) - Jing, Muzi; Fu, Yang; Fei, Xu; Tian, Jing; Zhi, Hui; Zhang, Haiyang; Xu, Longquan; Wang, Xiuying; Wang, Yi
Abstract : A simple one-pot method was developed to fabricate a novel hydrogel with good biocompatibility, excellent mechanical properties, and identifiability via photopolymerization and sol–gel processes. Abstract : Obtaining high strength hydrogels with good biocompatibility and identifiability is a challenging task. Herein, a new approach is presented that enables the simple one-pot synthesis of a high strength polymer hydrogel on the basis of silicone, poly(hydroxyethyl methacrylate) (PHEMA) and an Eu(iii ) organic complex. The composition and properties of the hydrogel could be easily tuned because of the good solubility of the monomers and non-interfering polymerization processes. The hydrogel exhibits an excellent integrated performance with toughness, high resilience, biocompatibility, and identifiability.